Laparoscopic Three-Port Sleeve Gastrectomy - Kirkil, Cueneyt; Aygen, Erhan; Aktimur, Recep; Korkmaz, Mehmet Fatih; Rzayev, Elshad (Mary Ann Liebert, Inc, 2018)
Aim: To assess and compare the practicability and efficacy of laparoscopic three-port sleeve gastrectomy (3PSG) and conventional laparoscopic sleeve gastrectomy (LSG). Materials and Methods: A prospectively constructed database of patients who underwent 3PSG (group 1) and conventional LSG (group 2), each containing 70 patients, was retrospectively analyzed. Results: The mean follow-up was 9.51.1 months for both groups. Mean operation time was longer in group 1 (47.2 +/- 8.9min vs. 40.7 +/- 7.5min, p<0.001). There were no intraoperative complications in either group. The median visual analogic scale was 2 (range, 1-5) in both groups (p>0.05). The mean narcotic analgesic rescue needs on the postoperative first and second days were less in group 1 (p<0.001, and p<0.05, respectively). Wound infection at 12mm port site was observed in 5 and 15 trocar sites in group 1 and group 2 (p<0.05), respectively. At mean 9.5 +/- 1.1 months follow-up, with no lost, excess BMI loss percentage (%EBMIL) was 69.3 +/- 29.7 in group 1, and 66.1 +/- 26.0 in group 2 (p>0.05). Conclusion: LSG can be performed without using of a retractor device inserted in a subxiphoid incision. 3PSG is a feasible technique without affecting EBMIL rates. It does not require highly experienced surgeons or special equipment in comparison with single incision laparoscopic surgery-sleeve gastrectomy.
Keywords: morbid obesity; sleeve gastrectomy; minimally invasive surgery; reduced port; laparoscopy; bariatric surgery